Trends in the use of echocardiography in pulmonary embolism. Issue 35 (August 2018) - Patel, Brijesh; Shah, Mahek; Garg, Lohit; Agarwal, Manyoo; Martinez, Matthew; Dusaj, Raman
Abstract : Abstract: Pulmonary embolism (PE) is a devastating diagnosis which carries a high mortality risk. Echocardiography is often performed to risk stratify patients diagnosed with PE, and guide management strategies. Trends in the performance of echocardiography among patients with PE and its role in influencing outcomes is unknown. We analyzed the 2005 to 2014 National Inpatient Sample Database to identify patients with primary diagnosis of PE or secondary diagnosis of PE and ≥1 of the following diagnoses: syncope, thrombolysis, acute deep vein thrombosis, acute cardiorespiratory failure, and secondary pulmonary hypertension. Trends in the performance of echocardiography and in-hospital mortality were analyzed. The admissions were divided into 2 groups with echocardiography, and without echocardiography, and 1:2 propensity score matching (PSM) was performed for comparison. The primary end-point was in-hospital mortality. The secondary endpoints were length of stay and total hospitalization costs. Odd ratios (OR) with confidence intervals (CI) were reported. A total of 299, 536 unweighted PE cases were studied. Performance of echocardiography among patients with PE patients increased from 3.5% to 5.6%, whereas in-hospital mortality decreased from 4.2% to 3.7% between years 2005 and 2014. Before matching, patients who received an echocardiogram were more likely to be younger, African American, admitted to a large, urban teaching institute, and had higher rates of concurrent acute deep vein thrombosis, and acute respiratory failure. Post-PSM, patients who received echocardiography during hospitalization had lower in-hospital mortality (odds ratio 0.75, 95% confidence intervals (CI) 0.68–0.83; P  < 0.001), longer length of stay (median 6 days vs 5 days; P  < .001) and higher mean hospitalization costs ($34, 379 vs $27, 803; P  < .001) compared to those without echocardiography. Performance of echocardiography among patients with a PE is increasing and is associated with lower in-hospital mortality. Abstract : Supplemental Digital Content is available in the text